The Subprime Mortgage Crisis: The Ramification of Financial Regulatory Failures - Wasli, Shahhidan (2009)
The subprime mortgage crisis has become somewhat a synonymous terminology with the mainstream media what with the economic debacle it had caused the world over. Vastly regarded as the catalyst to the plummeting United States economy at its lowest ebb in 2007, the calamity soon escalated to other global capital markets around the world and gradually depleting the regional economy considerably. What was preliminarily perceived as an innocuous setback to the U.S mortgage market had then escalated with a sizeable magnitude as the world faces the worst economic recession since the great depression in the 1930s when the stock market crashed in October 1929. The money market was severely impaired and many countries experienced considerable decline in their trading performances. Tantamount to that, the unemployment rate also peaks at its highest since 1983 while the global real Gross Domestic Products (GDP) and personal income show constant decline as the deteriorating state of economy persisted. Several perplexing questions and problems in relation to the subprime crisis will be assessed and substantiated to uncover the underlying issues. The weak regulatory structures and oversight as well as the financial governance faux pas are believed to be the root cause of the calamity. Whatever the bane of the crisis is, the main concern is whether the authority has done enough to get the economy back on track. As of now, the regulatory bodies and policy makers around the world are struggling to mitigate the setbacks in order to cushion the impact from further deteriorating the global capital market. As the dissertation progresses, there will be more extensive evaluation and study pertaining to the subject matter to assist in conclusive findings. These processes are broadly based on journal articles, literatures as well as statistical and academic studies.